Climate change negotiations and their implications for international development cooperation - Lars Engberg-Pedersen (Danish Institute for International Studies (DIIS), 2011)
This report discusses possible implications of the international attempts to address climate change for the organization of development cooperation. It concentrates on questions related to institutions and resources and pays less attention to potential consequences for the objectives and contents of development cooperation. The institutional question is limited to the norms, practices and organizations that emerge primarily at the international level in response to climate change. The resource question deals with the capital that needs to be mobilized to mitigate climate change and to finance the costs of adaptation to climate change in developing countries.
Keywords: 300; Klimaveränderung; Internationale Umweltpolitik; Internationale Zusammenarbeit; Neue Weltwirtschaftsordnung